Giving Breast Milk For Motoric Development For Babies In Karangtalun Village, Kalidawir District, Tulungagung On 2019 - Farida, Farida (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The research subjects were infants aged 6-9 months, as many as 61 infants with total sampling technique. Retrieval of data using questionnaire sheets and DDST II. Data is analyzed using the Chi-Square statistical test. The results of the study of 61 infants found 16 infants (26%) who received exclusive breastfeeding all had normal motor development. The majority of infants who received PASI had doubtful motor development, namely gross motorized 33 babies (54.1%) and fine motorcycles totaling 26 infants (42.6%). Obtained both gross and fine motor with a value of p = 0,000 and α = 0.05 which means the value (p value <α), meaning that there is a relationship between breastfeeding with motor development in infants aged 6-9 months. Exclusive breastfeeding is one of the factors that can affect motor development, because breast milk contains nutrients that help the process of motor development so that it develops optimally